1999
DOI: 10.1002/(sici)1097-0290(19990420)63:2<224::aid-bit11>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Production of Glomus intraradices propagules, an arbuscular mycorrhizal fungus, in an airlift bioreactor

Abstract: This work addresses the symbiotic culture of the arbuscular mycorrhizal (AM) fungus Glomus intraradices with Daucus carota hairy roots transformed by Agrobacterium rhizogenes, in two submerged culture systems: Petri dish and airlift bioreactor. AM fungi play an active role in plant nutrition and protection against plant pathogens. These fungi are obligate biotrophs as they depend on a host plant for their needs in carbohydrates. The effect of the mycorrhizal roots inoculum-tomedium volume ratio on the growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Such observation confirmed previous results obtained with in vitro cultures of various AM fungi [36,26]. Specifically focusing on G. intraradices , coefficients of variation calculated from different experiments ranked from 11%[37] to 22%[31], 38%[38] and even 61%[33]. The high variability observed in our experiment could be attributed to the host–fungus interaction and to both the fungal and plant physiology.…”
Section: Discussionsupporting
confidence: 91%
“…Such observation confirmed previous results obtained with in vitro cultures of various AM fungi [36,26]. Specifically focusing on G. intraradices , coefficients of variation calculated from different experiments ranked from 11%[37] to 22%[31], 38%[38] and even 61%[33]. The high variability observed in our experiment could be attributed to the host–fungus interaction and to both the fungal and plant physiology.…”
Section: Discussionsupporting
confidence: 91%
“…Knowing that AM carrot roots were limited in the C source after 8 weeks might indicate a relationship to the enhanced GDH activity found in the present study. Jolicoeur et al (1999) showed that carrot roots under in vitro conditions hydrolyzed all the sucrose contained in the medium after 25 days but that glucose and fructose then became available to the roots without being limiting even at low concentrations. It is then reasonable to assume that the highest GDH activities in AM roots might be related to a requirement for C skeletons, which would have led to a greater uptake of NH 4 + .…”
Section: Discussionmentioning
confidence: 99%
“…Diop et al (1994) used sheared roots as starter inoculum and produced 893 spores per plate in 3 months. The airlift bioreactor studied by Jolicoeur et al (1999) produced 12,400 spores per liter (approximately 375 spores in the equivalent volume of a split-plate compartment). This places in perspective the efficiency of the method of St-Arnaud et al (1996), which produced an average of 15,000 spores per distal side of a 9-cm-diameter split Petri dish (30 cm 3 ) 3-4 months after the fungus crossed the divider, 4-5 months total elapsed time.…”
Section: Discussionmentioning
confidence: 99%